Introductory forest science - Ratnasingam, Jegatheswaran (Universiti Putra Malaysia Press, 2014)
Forestry practices in Malaysia has come a long-way since the country's independence since 1957. The management of the forest resources has shifted away from primary wood production to a more holistic perspective involving economic, environmental and social aspects. The evolving phases in forestry practices in the country have been well documented in an earlier book entitled "Colonial British Forestry and the years thereafter". This INTRODUCTORY FOREST SCIENCE book is an attempt to present the complete array of subject matters involved in the study of forestry science in a single volume, Prepared specifically for first-year undergraduates in forestry curriculum throughout Malaysia and the region, it will also find acceptance among all those interested in the forest and its resources, Written by experts from the Faculty of Forestry at University Putra Malaysia(UPM), each chapter highlights the fundamentals, key-words, references and learning outcomes about the subject. Its easy reading makes it a useful introductory textbook for all those venturing into the field of forestry and should help invigorate their interests into the field of study